Step 1: We are given that \( P(B) \neq 0 \) and \( P(A | B) = 1 \). The conditional probability \( P(A | B) \) is defined as:
\[
P(A | B) = \frac{P(A \cap B)}{P(B)}.
\]
Since \( P(A | B) = 1 \), this implies:
\[
\frac{P(A \cap B)}{P(B)} = 1.
\]
Multiplying both sides by \( P(B) \), we get:
\[
P(A \cap B) = P(B).
\]
Step 2: The equation \( P(A \cap B) = P(B) \) means that the probability of the intersection of \( A \) and \( B \) is equal to the probability of \( B \). This implies that every outcome in \( B \) is also in \( A \), i.e., \( B \subseteq A \).
Thus, the correct conclusion is:
\[
B \subseteq A.
\]